Stability, performance and participatory evaluation of potato varieties under rain-fed and irrigation conditions at Southeast, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2025)
The goal of potato breeding is to develop widely adaptable, highly productive cultivars that farmers would prefer. The objective of this study was to evaluate the performance and stability of potato varieties linking the preferences of smallholder farmers in rain-fed and irrigated environments. Using a randomized complete block design in three replicates, twelve potato cultivars were assessed in 10 settings in Southeast Ethiopia during the Meher and Belg seasons in 2019 and 2020. The environments, genotypes, and GEI all revealed significant differences (p